The evolution of cultural competence theories in American (United States) nursing curricula: An integrative review - Alexander, Suzanne (J Nurs Educ Pract, 2020)
INTRODUCTION: Baccalaureate nursing students develop cultural competence through curricula of theories and frameworks which evolve to reflect new knowledge, but their synthesis and impact upon health quality outcomes is not known. METHODS: A cross-platform literature review was conducted to identify innovation and use of cultural competency theories and frameworks in nursing. Optimal literature included a formal theory, pedagogy, measures, and outcomes, which were then classified and evaluated. Additional perspectives and interventions were reviewed for potential influence on curricula and impact through the lens of integrative review. RESULTS: A shift in theory from essentialism to constructivism has occurred in undergraduate curricula. Challenges to measuring outcomes have been noted. All studies reported positive outcomes but suffer from self-selection, unvalidated instruments, and little to no longitudinal data. CONCLUSIONS: Nursing students are exposed to culturally competent care via several validated and canonical frameworks, but self-efficacy and long-term impact have not been assessed.